Analisis Tingkat Pendapatan Pedagang Sayur Lesehan di Pasar Medan Deli (Brayan) - Novia Ardila Siregar; Foeza Hafiz; Mitra Musika Lubis (Universitas Medan Area, 2021)
The purpose of this study is to find out what the level of income of traders vegetables and know the feasibility of the business of traditional vegetable traders in Medan Deli. The method of sampling is done by method intentionally (purposive sampling). Based on this study there are 114 population of vegetable traders, from the amount was determined as the researcher said that the sample size was not allowed less than 10% of the population but some said no less of 5%, but this benchmark is also not rigid, because of the large sample take a lot determined by other factors, so that obtained as many as 14 samples of vegetable traders who will be sampled. Data analysis method used is an analysis of costs, receipts, income and R / C with device aids microsoft excel. From the results of this study the R / C results of the vegetable traders is the result of the distribution of the total total cost of the lesehan vegetable trader in the amount of Rp.1,008,357, - while the total total receipts issued were Rp.1,144,179, - and the income of vegetable traders averaged Rp. 135,821 thus the total number of average R / C traders is 1.15. This means vegetable traders in running a vegetable business that will receive acceptance amount to 1.15 rupiah for every 1 rupiah spent (vegetable traders business already feasible because the R / C of all traders is more than 1). Then trade vegetables at the Medan Deli (Brayan) Market are said to be suitable for sale or run.